1999
DOI: 10.1016/s0002-9270(99)00040-4
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound cannot determine suitability for esophagectomy after aggressive chemoradiotherapy for esophageal cancer

Abstract: When aggressive preoperative chemoradiotherapy is provided to patients with esophageal cancer, the predictive value of postchemoradiotherapy EUS is inadequate for use in clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 19 publications
2
61
0
1
Order By: Relevance
“…Moreover, 63 patients (38%) received preoperative neoadjuvant chemotherapy, and these patients' tumours may have been down-staged, further influencing the potential accuracy of both the CT and EUS stage. Indeed, the strengths of agreement between both EUS T and N stage were better in patients who had undergone surgery alone (T stage Kw=0.696 and N stage Kw 0.569) compared with patients who had received neoadjuvant chemotherapy (T stage Kw=0.364, and N stage Kw=0.459, respectively), which is consistent with previous reports [2,9,[17][18][19][20]. Nevertheless, the study also has strengths in that it represents an original prospective study of 9 years of pragmatic specialist multidisciplinary upper GI practice by experienced clinicians with wellaudited and published results [9,11,21].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, 63 patients (38%) received preoperative neoadjuvant chemotherapy, and these patients' tumours may have been down-staged, further influencing the potential accuracy of both the CT and EUS stage. Indeed, the strengths of agreement between both EUS T and N stage were better in patients who had undergone surgery alone (T stage Kw=0.696 and N stage Kw 0.569) compared with patients who had received neoadjuvant chemotherapy (T stage Kw=0.364, and N stage Kw=0.459, respectively), which is consistent with previous reports [2,9,[17][18][19][20]. Nevertheless, the study also has strengths in that it represents an original prospective study of 9 years of pragmatic specialist multidisciplinary upper GI practice by experienced clinicians with wellaudited and published results [9,11,21].…”
Section: Discussionsupporting
confidence: 91%
“…The EUS staging accuracy (overall T = 39%, N = 58%) after NAC in our study was comparable with that in other published series [1,[3][4][5]9]. Several, mostly small, studies over the past decade have attempted to address the role of EUS after NAC by comparing various variables of the tumor such as size and T and N staging, or by comparing the post-NAC EUS results with surgical pathology.…”
Section: Discussionsupporting
confidence: 86%
“…In a study of 99 patients receiving NAC for gastroesophageal cancer, EUS was able to detect only two of the eight patients who had complete absence of tumor tissue (surgical pathology of T0N0) [13]. A similarly low accuracy for detecting the absence of tumor tissue after chemoradiation was shown as well [3]. T-stage to histologic T-stage Histologic T0 T1 T2 T3 T4 T0 0 In our study, none of the 17 patients who demonstrated absence of residual tumor tissue after chemotherapy were accurately identified by EUS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, even when EUS and CT scan were combined, inaccuracies still were present in 32% of cases. The accuracy of EUS can be even further diminished if chemotherapy or radiotherapy has been administered previously [14].…”
Section: Discussionmentioning
confidence: 99%